Cystic Adventitial Disease of Popliteal Artery: Case Report - Meecham, Lewis; Wright, Anna; Atwal, Amarjit (International Journal of Angiology, 2016)
Cystic adventitial disease (CAD) is a rare cause of arterial stenosis. A total of 85% of cases are usually found in the popliteal artery. Men in their fourth and fifth decade are more commonly affected. If untreated the disease will progress eventually ending in occlusion of the affected vessel and limb-threatening ischemia. With this in mind an effective and long-lasting treatment is required, and here we present a case with CAD of the popliteal artery and discuss the merits of different treatment strategies.
Keywords: claudication; popliteal artery; peripheral arterial disease; percutaneous